Attitudes of Canadian Plastic Surgeons on Temporal Artery Biopsy in Giant Cell Arteritis Management. Issue 7 (20th July 2021) - Lafreniere, Ann-Sophie; Hartley, Rebecca; Ponich, Brett; Nickerson, Duncan; Temple-Oberle, Claire F.
Abstract : Background: Temporal artery biopsies (TAB) rarely impact management of patients with suspected giant cell arteritis and carry complications. We sought plastic surgeons' perspectives on this procedure's risks and benefits. Methods: An email survey was designed, piloted, and refined to elicit Canadian Society of Plastic Surgeons (CSPS) members about TAB's diagnostic contribution, complications, usefulness as a resident education tool, and surgeons' insight into emerging diagnostic modalities like ultrasound. Text comments were sought at each question. A reminder was emailed one week later. Data was compared and analyzed using the chi-squared test and student t -test. Results: An estimated 83 responses were received from 435 surgeons (19%). Of the surgeons, 20% voiced uncertainty regarding TAB indications; 40% were unsure if TAB results changed steroid duration and dose; 83% did not see patients postoperatively. Surgeons recalled 29 cases of hematoma and three facial nerve injuries from TAB. In total, 80% felt TAB was a valuable learning opportunity for residents, although residents were involved in only 21% of cases; 65% of surgeons supported a changeover to ultrasound as primary diagnostic modality. Analysis of text comments revealed a sense of futility from TAB and disdain toward being mere technicians. Several participants wished for stakeholders to collaborate and potentially endorse noninvasive diagnostic modalities. Conclusions: This survey demonstrated varying attitudes to TAB. Generally, plastic surgeons were uncertain of TAB's contribution to treatment, tended not to follow-up on results or patients, and recognized a number of complications. Conversations are desired regarding switching from scalpel to probe to evaluate the temporal artery.